Energy and Macronutrients Intakes among Childbearing Age Women Living in the Urban Area of Morocco: A Cross-Sectional Study - Fatima Barich; Fatima Zahra Laamiri; Slimane Mehdad; Souad Benaich; Anass Rami; Mohamed Idrissi; Chaimae Serbouti; Houria Lahmame; Hasnae Benkirane; Manelle Rjimati; Amina Barkat; El Arbi Rjimati; et al. (Journal of Nutrition and Metabolism)
Over the last few decades, there have been significant dietary and lifestyle changes worldwide. In Morocco, these changes have led to serious nutritional disorders and increased risk of morbidity and mortality particularly among vulnerable groups such as women of childbearing age. We aimed to assess the average daily energy and macronutrient intakes and to investigate their association with socioeconomic factors and weight status among women aged 19–49 years in urban areas. A total of 542 women attending public health centers were recruited. Socioeconomic and demographic data were collected using a questionnaire. Anthropometric measurements were taken using standardized equipment. Food consumption data were obtained through the 24-hour dietary recall method, and the macronutrient composition of foods was estimated based on the Moroccan food composition table and the Nutrilog software. The average daily energy intake among the study population was 1591 kcal, composed of 56% from carbohydrates, 28% from fats, and 16% from protein. Reported energy intake by the majority of women (81.5%) was lower than recommended daily allowances for energy. There was a significant positive correlation between educational level and energy (p=0.001), carbohydrates (p=0.001), proteins (p=0.004), and fats intakes (p=0.032), respectively. A significant negative association of household size with protein intakes was also observed (p=0.034). Carbohydrates, proteins, and fats intakes tended to decrease; however, these associations were not statistically significant. Further studies and appropriate interventions are needed to address the trends in energy and macronutrients intakes in the development of policy initiatives aimed at nutrition education and chronic disease prevention among childbearing age women.